Edukasi Kalimat Efektif sebagai Upaya Meningkatkan Keterampilan Menulis Siswa Kelas X BR 3 SMK Negeri 3 Balikpapan - Ari Musdolifah; Rika Istianingrum; Deden Deden; Prita Indriawati; Nurliani Maulida; Kiftian Hady Prasetya (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2023)
Effective sentences are foundations in writing skills. However, there are still many students who have not applied the effective sentence t-shirt correctly. One inhibiting factor in the lack of knowledge about effective sentences is the lack of knowledge about effective sentences. There needs to be activities to support this knowledge. The effort made is education to students about effective sentences. The aim is to improve students' writing skills in effective sentences. The method used in Community Service (PkM) is the method of lecture and discussion. This method is used to improve students' analytical abilities against sentences. This activity is carried out with four stages, namely preparation, implementation by counseling by providing material: understanding, type, characteristics, and examples of effective sentences, as well as evaluation, and preparation of reports. The organizer of this activity is the Balikpapan University FKIP Lecturer. Participants in this activity are class X RB 3 State Vocational High School 3 Balikpapan. This activity was carried out in class X RB 3, address on Belibis Street number 100, South Balikpapan, East Kalimantan. The result of this activity is that students can write effective sentences characterized by 70% structural equivalence, 70% compatibility of forms, 80% economy of words, 60% accuracy of reasoning, 60% cohesiveness of ideas, and 75% logicality of language.